(untitled) (Bangladesh Journal of Zoology, 2021)
Prevalence of some common human traits viz., body weight, height and body mass index (BMI), pattern baldness, body hair, chin, colour blindness, cheek dimples, earlobes, length of index finger, lips, nose, polydactyly, tongue and widow’s peak, and ABO blood groups along with their Rh-D antigen, were recorded and analyzed from 500 male and 1000 female students of the Rajshahi University (RU) Campus. Results showed that body weights of the male students (66.42±8.92 kg) were significantly higher (t= 35.14; P<0.001) than those of the female students (51.64±6.97 kg). The differences in BMI between males (23.32±3.26) and females (20.85±2.63), as expected, were also highly significant (t= 15.79; P<0.001) and notably, some of the female students were underweight (BMI< 18.5). No female had baldness compared to 15.8% bald males. Sparse body hair was prevalent over the dense body hair in both genders. The females had much higher smooth chin (89.6%) than the males (58.0%) but the males had much higher cleft chin (42.0%) compared to the females (10.4%). No female was colourblind whereas 7.4% males were colourblind. Absence of dimples was recorded in 92.4% males and 85.7% females. Attached earlobes were higher than the free earlobes in both sexes. Compared to the length of the ring finger, shorter index finger was prevalent both in males (85.4%) and females (68.6%). Frequencies of the broad lips in males and females were 53.4% and 58.6%, respectively. Females dominated large and broad noses (76.1%) in comparison with their male counterparts (61.4%). Polydactyly was a rare trait in the Campus, where only 2.2% males and 0.2% females had extra digits in their hands or feet. Tongue rollers (53.8%) outnumbered the tongue folders in males, but tongue folders (54.4%) outnumbered the tongue rollers in females. Males with widow’s peak were higher (25.8%) than that in the females (19.0). Blood groups in the males and females were in the order: B (32.0) > O (29.8) > A (22.4) > AB (15.8) and O (34.8) > B (34.4) > A (21.9) > AB (8.9), respectively. As a whole, 85.4% males and 98.0% females were Rh-positive where the blood group phenotypes did not affect body weight, height and BMI of the subjects (r=0.012; P=0.63). The relevance of these findings to the physical, physiological, social and clinical well-being of the humans has been discussed. Bangladesh J. Zool. 49 (2): 215-228, 2021